Parasite community of a temporal notothen fish from intertidal rocky pools in south-central Chile: Is it similar to other fish from the same habitat? (Revista de Biología Marina y Oceanografía, 2018)
Notothen fishes (Nototheniidae) have been recorded on the coasts of South America, from 35°S to southern. Little is known about the biology of intertidal notothen fishes or their relationships with other species, including parasites. Here, we analyzed the parasitic fauna of a species of Notothenia collected from the rocky intertidal of Lebu, south-central Chile (36°S) and compared the parasite community of this host with other 9 fish species commonly found in rocky intertidal pools. Among the tested species, Notothenia sp. had the highest parasite richness (21 parasitic taxa vs. 1 to 9 parasitic taxa). The composition of parasite species was different among fishes, with similarity indices between 0 and 33%. The parasite composition of Notothenia sp. was most similar to Calliclinus geniguttatus (27%). The most abundant and prevalent parasites found in Notothenia sp. were the copepod Caligus cf. cheilodactyli, Tetraphyllidea larvae, anisakid nematodes, and several acanthocephalan species, which are typical of other fish from the subtidal and bento-demersal zones. Therefore, we conclude that the juveniles of Notothenia sp. were a few months old and had their parasites when reaching the intertidal zone, acquired some generalist parasites during their stay in this habitat, such as Holobomolochus chilensis and Lecithaster macrocotyle. Most notothen fishes are from Antarctic and Sub-Antarctic waters, therefore, it is possible that this fish came from another habitat but also from the austral region of South America. Notothenia sp. could not be specifically identified because of different results between morphological and genetic analyses.